Respuesta :

Answer:

Since the given relation is proportional, the value of s multiplied by the constant of proportionality will be the value of P

we can write the above statement as:

s * k = P   (where k is the constant of proportionality)

putting some given proportional values of s and P

2 * k = 8

k = 8 / 2

k = 4

Now that we have the constant of proportionality, we can use it in the equation we just made

s * k = P

s (4) = P

4s = P

This is the relationship between s and p, represented by an equation

Answer:

Since the given relation is proportional, the value of s multiplied by the constant of proportionality will be the value of P

we can write the above statement as:

s * k = P   (where k is the constant of proportionality)

putting some given proportional values of s and P

2 * k = 8

k = 8 / 2

k = 4

Now that we have the constant of proportionality, we can use it in the equation we just made

s * k = P

s (4) = P

4s = P

This is the relationship between s and p, represented by an equation